(untitled) (Analysis in Theory and Applications, 2022)
In this note, we obtain sharp L^p estimates of parametric Marcinkiewicz integral operators. Our result resolves a long standing open problem. Also, we present a class of parametric Marcinkiewicz integral operators that are bounded provided that their kernels belong to the sole space L^1( S^n-1) .